2022
DOI: 10.1038/s41586-022-04712-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and chemotherapeutic influences on germline hypermutation

Abstract: Mutations in the germline generates all evolutionary genetic variation and is a cause of genetic disease. Parental age is the primary determinant of the number of new germline mutations in an individual’s genome1,2. Here we analysed the genome-wide sequences of 21,879 families with rare genetic diseases and identified 12 individuals with a hypermutated genome with between two and seven times more de novo single-nucleotide variants than expected. In most families (9 out of 12), the excess mutations came from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 72 publications
7
76
1
Order By: Relevance
“…Populations of great apes, mice, and yeast have similarly distinctive mutational processes (Lindsay, et al 2019;Jiang et al 2021;Goldberg and Harris 2022). It remains unclear how much these changes are due to evolution of the underlying genome-replication machinery versus changes in life history or exposure to environmental mutagens (Mathieson and Reich 2017;Macià et al 2021;Ruis, Peacock, et al 2022;Ruis, Weimann, et al 2022)-although in a few cases changes in the mutation spectrum have been linked to heritable genetic change affecting the function or expression of proteins involved in genome replication or repair (Couce et al 2013;Jiang et al 2021;Robinson, et al 2021;Kaplanis et al 2022;Sasani et al 2022). For viruses, the mutational process can also be affected by a virus's ability to evade host innate-immune proteins that mutagenize viral nucleic acids (Sadler et al 2010;De Maio et al 2021;Ratcliff and Simmonds 2021;Ringlander et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Populations of great apes, mice, and yeast have similarly distinctive mutational processes (Lindsay, et al 2019;Jiang et al 2021;Goldberg and Harris 2022). It remains unclear how much these changes are due to evolution of the underlying genome-replication machinery versus changes in life history or exposure to environmental mutagens (Mathieson and Reich 2017;Macià et al 2021;Ruis, Peacock, et al 2022;Ruis, Weimann, et al 2022)-although in a few cases changes in the mutation spectrum have been linked to heritable genetic change affecting the function or expression of proteins involved in genome replication or repair (Couce et al 2013;Jiang et al 2021;Robinson, et al 2021;Kaplanis et al 2022;Sasani et al 2022). For viruses, the mutational process can also be affected by a virus's ability to evade host innate-immune proteins that mutagenize viral nucleic acids (Sadler et al 2010;De Maio et al 2021;Ratcliff and Simmonds 2021;Ringlander et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Mutational signature analysis can be used to decipher the potential mutational processes underlying individual cancer or germline hypermutation [ 52 , 53 ]. A recent study has revealed genetic and environmental contributions to the germline dn SNV hypermutation [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutational signature analysis can be used to decipher the potential mutational processes underlying individual cancer or germline hypermutation [ 52 , 53 ]. A recent study has revealed genetic and environmental contributions to the germline dn SNV hypermutation [ 53 ]. Our study explored the utility of mutational signature analysis to decode potential mutational processes in the context of dn CNV hypermutation.…”
Section: Discussionmentioning
confidence: 99%
“…CC-BY 4.0 International license perpetuity. It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted December 17, 2022. ; https://doi.org/10.1101/2022.12.17.520885 doi: bioRxiv preprint dataset of 903,525 de novo single-nucleotide variant calls (dnSNVs) (detailed in (Kaplanis et al, 2022)). After filtering to remove 20 hyper-mutated and other outlier individuals by looking at the zscore of DNM counts, this resulted in a dataset comprising 210,918 dnSNVs called in 10,749 trios, which were then phased by parent of origin (using reads and nearby informative heterozygous sites).…”
Section: Datamentioning
confidence: 99%